Knockdown of ARL5B Induces Mitochondrial-mediated Apoptosis and Inhibits Glycolysis in Breast Cancer Cells by Activating MDA5 Signaling - Zhang, Lei; Hu, Xuqiao; Wu, Huaiyu; Tian, Hongtian; Zeng, Jieying; Song, Di; Yang, Keen; Chen, Jing; Xu, Jinfeng; Dong, Fajin (Current Cancer Drug Targets, 2022)
Aim: Mitochondria are essential for energy metabolism in the tumor microenvironment and the survival of cancer cells. Background: ADP-ribosylation factor–like GTPase 5b (ARL5B) has been found to be associated with mitochondrial dysfunction and breast cancer (BC) progression, but the underlying mechanism needs to be further understood. Objective: We investigated the effects of ARL5B on the apoptosis and glycolysis of breast cancer cells and its underlying mechanisms. Methods: Quantitative reverse transcription-PCR (qRT-PCR) and western blot assays were used to detect the expression of ARL5B in breast cancer tissues and cells. An ARL5B loss-of-function assay was performed to verify its role in BC development. Results: ARL5B was upregulated in breast cancer tissues and cell lines. ARL5B knockdown induced apoptosis and activated the mitochondrial pathway in breast cancer cells. Interestingly, the inhibition of ARL5B repressed the aerobic glycolysis of breast cancer cells. The role of ARL5B in breast cancer cells was exerted by mediating the activation of viral RNA sensor MDA5-evoked signaling. Silencing ARL5B triggered MDA5 signaling by upregulating the key proteins involved in the MDA5 pathway. Importantly, MDA5 silencing reversed the effects of ARL5B knockdown on mitochondrial-mediated apoptosis and glycolysis, whereas poly (I:C), as a ligand for MDA5, further enhanced ARL5B knockdown- facilitated mitochondrial apoptosis and the inhibition of glycolysis. Conclusion: The knockdown of ARL5B activated MDA5 signaling and thus led to the enhanced mitochondrial- mediated apoptosis and glycolysis inhibition in breast cancer cells. Our study suggested that ARL5B might be a potential therapy target for BC.
Keywords: mitochondria